Allosteric Inhibitors of the Eya2 Phosphatase Are Selective and Inhibit Eya2-mediated Cell Migration - Krueger, Aaron B. (American Society for Biochemistry and Molecular Biology, 2014)
Eya proteins are essential co-activators of the Six family of transcription factors and contain a unique tyrosine phosphatase domain belonging to the haloacid dehalogenase family of phosphatases. The phosphatase activity of Eya is important for the transcription of a subset of Six1-target genes, and also directs cells to the repair rather than apoptosis pathway upon DNA damage. Furthermore, Eya phosphatase activity has been shown to mediate transformation, invasion, migration, and metastasis of breast cancer cells, making it a potential new drug target for breast cancer. We have previously identified a class of N-arylidenebenzohydrazide compounds that specifically inhibit the Eya2 phosphatase. Herein, we demonstrate that these compounds are reversible inhibitors that selectively inhibit the phosphatase activity of Eya2, but not Eya3. Our mutagenesis results suggest that this class of compounds does not bind to the active site and the binding does not require the coordination with Mg(2+). Moreover, these compounds likely bind within a site on the opposite face of the active site, and function as allosteric inhibitors. We also demonstrate that this class of compounds inhibits Eya2 phosphatase-mediated cell migration, setting the foundation for these molecules to be developed into chemical probes for understanding the specific function of the Eya2 phosphatase and to serve as a prototype for the development of Eya2 phosphatase specific anti-cancer drugs.